2020
DOI: 10.3168/jds.2019-17543
|View full text |Cite
|
Sign up to set email alerts
|

Validating a heat stress model: The effects of an electric heat blanket and nutritional plane on lactating dairy cows

Abstract: The efficacy of an electric heat blanket (EHB) has previously been confirmed as an alternative method to evaluate heat stress (HS). However, a pair-feeding design has not been used with the EHB model. Therefore, study objectives were to determine the contribution of the nutritional plane to altered metabolism and productivity during EHB-induced HS. Multiparous Holstein cows (n = 18; 140 ± 10 d in milk) were subjected to 2 experimental periods (P); during P1 (4 d), cows were in thermoneutral conditions with ad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
(101 reference statements)
8
9
0
Order By: Relevance
“…To better understand the direct impact of heat stress on dairy cows, specific experimental methods should be used, such as a climate control chamber system or an electric blanket, for dairy cow studies [63,64]. To elucidate the functional outcome from heat stress-induced impaired immune response, immune challenges model could be applied for future study.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the direct impact of heat stress on dairy cows, specific experimental methods should be used, such as a climate control chamber system or an electric blanket, for dairy cow studies [63,64]. To elucidate the functional outcome from heat stress-induced impaired immune response, immune challenges model could be applied for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle protein catabolism makes available gluconeogenic precursors to fuel-activated immune cells (Wannemacher et al, 1980) and provides additional amino acids for APP synthesis (Iseri and Klasing, 2013), although, as aforementioned, we curiously did not detect an increase in circulating APP. Consequently, protein metabolism is affected by HS, as muscle catabolism biomarkers such as BUN are increased during HS (Yoshizawa et al, 1997;Yunianto et al, 1997;Pearce et al, 2013a;Al-Qaisi et al, 2020). In agreement, BUN levels were increased in HS steers irrespective of the Zn form fed and substantially increased compared with the PF steers, although ZAHS had numerically reduced BUN relative to ZSHS, whereas ZAHS did not statistically differ from ZSCON, ZSPF, or ZAPF BUN values.…”
Section: Discussionmentioning
confidence: 55%
“…The increase in NEFA is bioenergetically expected, because both groups were on a lowered plane of nutrition, and adipose mobilization is a homeorhetic response to maintain energy supply for metabolic processes. Our group has previously reported that heat-stressed ruminants do not mobilize as much adipose tissue as their PF counterparts (Rhoads et al, 2009;O'Brien et al, 2010;Al-Qaisi et al, 2020). In this study, we utilized an ad libitum control, and this likely explains why we detected a small increase in NEFA in HS steers.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, our study represents natural changes of immunity of two breeds of dairy cow in the mid-lactation period from normal to heat-stress environmental conditions. To better understand the direct impact of heat stress on immune responses, in future studies, a chamber system or electric blanket should be applied to induce heat stress [37,78]. In this study, we found several altered genes related to critical immune functions in dairy cows by high THI environmental condition.…”
Section: Discussionmentioning
confidence: 64%